"She goes into character as the lady of the house": tour guides, performance, and the Southern plantation. Issue 3 (2nd July 2016) - Potter, Amy E.
ABSTRACT: Research has shown how little tour guides in the American South talk about slavery and the enslaved during plantation home tours. However, most of this literature fails to interview the guides directly and consider their perspectives. This research builds upon this work but ultimately diverges by taking a different methodological approach, interviewing 28 docents working at four Louisiana plantation homes on River Road (Oak Alley, Laura, Houmas House, and San Francisco) in an effort to foreground their voices and experiences. Incorporating the work of performativity, this paper seeks to draw out the nuances of plantation tours and move beyond the reading of the tour as text or script. This paper will challenge the assumption that all tours within a single home, even with the same guide, are the same, adding to the complexity of conducting research on this topic. This complexity is also present in the ways slavery and the contributions of the enslaved are absent or woven within a house tour to varying degrees. In order to better address the symbolic annihilation of African-Americans occurring within these homes, we must understand not only the various degrees of control guides exercise over their tour, but also the tour as a complex performance, ephemeral and unpredictable in nature.